Cartilage‐targeting ultrasmall lipid‐polymer hybrid nanoparticles for the prevention of cartilage degradation. Issue 1 (10th September 2020) - Ai, Xiangzhao; Duan, Yaou; Zhang, Qiangzhe; Sun, Derrick; Fang, Ronnie H.; Liu‐Bryan, Ru; Gao, Weiwei; Zhang, Liangfang
Abstract: Current drug delivery approaches for the treatment of cartilage disorders such as osteoarthritis (OA) remain inadequate to achieve sufficient drug penetration and retention in the dense cartilage matrix. Herein, we synthesize sub‐30 nm lipid‐polymer hybrid nanoparticles functionalized with collagen‐targeting peptides for targeted drug delivery to the cartilage. The nanoparticles consist of a polymeric core for drug encapsulation and a lipid shell modified with a collagen‐binding peptide. By combining these design features, the nanoparticles can penetrate deep and accumulate preferentially in the cartilage. Using MK‐8722, an activator of 5′‐adenosine monophosphate‐activated protein kinase (AMPK), as a model drug, the nanoparticles can encapsulate the drug molecules in high capacity and release them in a sustained and controllable manner. When injected into the knee joints of the mice with collagenase‐induced OA, the drug‐loaded nanoparticles can effectively reduce cartilage damage and alleviate the disease severity. Overall, the ultrasmall targeted nanoparticles represent a promising delivery platform to overcome barriers of dense tissues for the treatment of various indications, including cartilage disorders. Abstract :